Terrorismusbekämpfung in Westeuropa. Demokratie und Sicherheit in den 1970er und 1980er Jahren - Hürter, Johannes (Quellen und Darstellungen zur Zeitgeschichte, 2015)
Researchers in contemporary history have only recently turned their attention to government activities to combat ´old` terrorism and its socio-cultural implications. This compendium takes a much-needed next step by comparing the history of confrontation between democracy and terrorism and examining different anti-terrorism policies in the context of international relations.